PRESERVATION OF THE HERITAGE VALUES OF IRAQI TRADITIONAL HOUSES - Abdulhussein Al-Ghalib, Ali; Sadiq Al-Assadi, Laith (Journal of Engineering and Sustainable Development, 2018)
The traditional Iraqi (Baghdadi) houses were being formed over centuries of effort and contribution and reached their final shape at the end of the nineteenth century. These masterworks have nowadays arrived at a critical stage. The fundamental problem with these houses is that they were all built with non-durable materials, such as clay brick, timber, and mud with straws. Therefore, the majority has been ruined; very few survived or should be saved for the future. The survivors should be conserved in a vigorous way to maintain their heritage values. Unfortunately, in Iraq to date, the process of dealing with historical buildings is rather artless and immature for various reasons. As a first conservation rule, it is always said that there are no rules; however, there is a group of standard ethics and principles that must be thoroughly taken into consideration in conservation. The conservation ethics and principles are given in the context of this paper. Every technical decision made should be assessed alongside the principles and ethics. Given that the number of this type of historical structure is not rare, the paper aims at setting standards and rules to facilitate the mission of conservation. Despite the sheer volume of such houses in the old dense zones of Baghdad, their structure is quite simple, and original materials are advantageously identified. Some common structural defects along with their repair procedure are reviewed in this paper.